A study for the genotoxicity assessment of substances containing probiotic candidates in the in vitro TK6 cell micronucleus test: Influence of low pH conditions and antibiotic supplementation on the test results - Yohei Fujiishi; Wakako Ohyama; Emiko Okada (Genes and Environment)
Abstract Background When assessing the genotoxicity of substances containing probiotic candidates, such as lactic acid-producing bacteria, using the in vitro micronucleus test (MNT), bacterial growth in the test medium may reduce the pH of the medium. The low medium pH is known to induce cytotoxicity and false-positive results. In the TK6 cell system, it is difficult to completely remove the bacteria from the medium by washing post-treatment, leading to bacterial growth during the recovery period in the short-term treatment. In the present study, the low pH range yielding false positives in the TK6 cell MNT was investigated using media supplemented with acetic, lactic, or formic acids, which are non-genotoxic bacterial metabolites. Additionally, to suppress the bacterial growth during the recovery period using antibiotics, i.e., penicillin/streptomycin (P/S), gentamicin sulfate (GM), and amphotericin B (AP), the maximum applicable concentrations of them that did not affect TK6 cell growth or micronucleus induction were determined. Then, we conducted an MNT using a substance containing live lactic acid-producing bacteria to verify the effectiveness of the antibiotics. Results Acetic, lactic, and formic acids induced micronuclei in TK6 cells (false positive) at an initial pH of ≤ 6.2 and ≤ 6.0 in 3 h treatment with and without S9 mix, respectively, and of ≤ 6.7 in the continuous treatment. Media supplemented with P/S, GM, and AP did not affect TK6 cell growth or micronucleated cell frequencies in the negative and positive controls ≤ 400 unit/mL-400 µg/mL, ≤ 250, and ≤ 20 µg/mL, respectively. In an MNT with fermented milk containing live lactic acid-producing bacteria, supplementation with P/S or GM to media for the recovery cultures suppressed the bacterial growth, decreasing pH, and cytotoxicity. Conclusion This study revealed the low pH ranges yielding false positives in the TK6 cell MNT under short-term and continuous treatment conditions. These values will serve as references for interpreting the biological relevance of results. Under short-term treatment, optimal antibiotic supplementation in recovery cultures suppressed bacterial growth in the test substance and prevented the decrease in pH that could yield false positives. This approach might be useful for evaluating the genotoxicity of test substances containing probiotic candidates using the MNT.